Cosplay As a Youth Subculture: The Factors of Choice and Identity Formation - Abramova, S.; Smirnova, O.; Tataurova, S. (KnE Social Sciences, 2021)
The article addresses the establishment and peculiarities of cosplay as a youth urban subculture in modern Russia. Cosplay is referred to as a subculture created by young people specifically for themselves, which, in a sense, defines it as elitist as long as it is aimed to form a relatively closed community. The authors demonstrate the possibilities of conducting a sociological analysis of cosplay by means of methodologies of sociology of recreation, sociology of game, sociology of communication and sociology of subculture, which supports a multidisciplinary approach to understanding of new practices in youth subcultures. The study actualizes the problem of constructing a new type of identity through subculture, while enhancing such aspects of cosplay as values and norms, and culture and behavior. The subculture analysis relies on the results of multi-methodological, empirical research in sociology: a mass survey (n=496) and in-depth interviews (n=10) conducted in 2018 with cosplayers in Russia. The techniques of on-line survey and face-to-face interview were used. The study reveals basic motives of cosplayers at the stages of entering the subculture and subculture affiliation; addresses the criteria of self-identification as cosplayers and characterizes the attitude of their immediate environment to the choice of this specific subculture. The low level of identifying cosplay with subculture and the absence of opposition to mainstream societal norms and values is one of the most significant conclusions, which corresponds to growing urban tolerance towards displays of subcultures, the rise of cosplay positive connotations in mass media and reference groups. Furthermore, cosplayers give recreational and communicative components of cosplay priority, thus making cosplay a cultural and ludic “hybrid phenomenon”. This study is one of the pioneering ones to research cosplay in Russia, which accounts for its particular relevance and salience. Keywords: cosplay, subculture, motivation, playisation, recreation